Energy Production in the Mississippi River Delta Impacts on Coastal Ecosystems and Pathways to Restoration - Day, J. W.; Hunter, R. G.; Clark, H. C. (Lecture Notes in Energy, 2022)
XI, 242 p. 99 illus., 77 illus. in color.